(untitled) (TAJ: Journal of Teachers Association, 2019)
Phaeochromocytomas are the rare tumors of the adrenal gland arising from the chromaffin cells of the adrenal medulla. These patients usually presents with triad symptoms of hypertension, headache and palpitation although there are some other presenting features like sweating, pallor, weight loss, hyperglycemia, nausea and psychological effects. 5 Ps- indicates Pressure (blood pressure), Pain (headache), Perspiration (sweating) Palpitation and Pallor can also be the presenting features. It is one of the surgically correctable hypertension. Diagnosis is made biochemically and localization is done by various imaging techniques such as USG, CT, MRI and I-MIBG. Extra adrenal tumors can be detected by-IMIBG. Localization is very much essential for planning of the surgery. Cytology or histopathology can not differentiate malignant from benign Phaeochromocytoma as both reveals similar features of pleomorphism, mitosis and atypical nucleus. Malignant Phaeochromocytoma can be distinguished by invasion of the adjacent structures, documenting nodal and distant metastasis. Treatment is essentially surgery either open or laparoscopic. Preoperative care is the most important part of treatment which include control of hypertension and alpha blockade adequate hydration with IV fluid. Per operative monitoring of cardiac and haemodynamic status is also very important part of treatment. HDU or ICU management may be necessary in the early post operative days. TAJ 2010; 23(1): 67-70